Succinonitrile as a high‐voltage additive in the electrolyte of LiNi0.5Co0.2Mn0.3O2/graphite full batteries. (21st December 2019) - Han, Songyi; Liu, Yan; Zhang, Hong; Fan, Chaojun; Fan, Weizhen; Yu, Le; Du, Xueyong
Abstract : As a functional additive, succinonitrile (SN) can be used in LiNi0.5 Co0.2 Mn0.3 O2 /graphite lithium ion batteries to broaden the oxidation electrochemical window of the electrolyte and significantly improve its rate performance and high‐voltage cycle performance. Linear sweep voltammetry (LSV) shows that EC/EMC‐based electrolytes with SN have higher oxidation potentials (approximately 6.1 V vs Li/Li + ). The capacity retention of LiNi0.5 Co0.2 Mn0.3 O2 /graphite full cell with 0.5‐wt% SN added to the electrolyte and 120 cycles between 2.75 and 4.4 V was significantly increased from 67.96% to 84.0%. It is indicated that the LiNi0.5 Co0.2 Mn0.3 O2 (NCM523) battery containing 0.5‐wt% SN‐based electrolyte has better cycleability and capacity retention at high cutoff voltage. In addition, electrochemical impedance spectroscopy (EIS), scanning electron microscopy (SEM), and X‐ray photoelectron spectroscopy (XPS) of the full cell were used to characterize the effect of SN on the cell. It is proved that the SN participates in the interfacial reaction between the electrode and the electrolyte to form a stable solid electrolyte interphase (SEI) layer, thereby effectively suppressing the increase of the charge transfer resistance and reducing the elution of the transition metal cations. These results indicate that SN can be used as a functional additive for high‐voltage lithium‐ion batteries.